Kontribusi agen dan faktor penyebab kejadian luar biasa keracunan pangan di Indonesia: kajian sistematis - Risalia Reni Arisanti; Citra Indriani; Siswanto Agus Wilopo (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Contribution of agents and factors causing foodborne outbreak in Indonesia: a systematic review PurposeThe purpose of this study is to understand burden of foodborne outbreak in Indonesia during 2000 -2015. MethodSystematic review conducted based on publish and unpublished (grey literature) data during 2000 -2015. Publish data from search engine such as Google scholar, open access, repository online university in Indonesia. Grey literature collected from investigation report from selected university (UGM, UI and UNAIR), Ministry of Health, Food and Drug Administration (BPOM) Indonesia. 2 reviewer will select and extract relevant data. ResultsDuring 2000 – 2015 there was 1.176 foodborne outbreak with West Java Province as the highest event with 61.119 foodborne cases (AR: 8.5%) and 291 deaths (CFR: 0.4%). Women have more risk on foodborne with proportion 58.3%. Daily meal (36.6%) and special celebration (29.7%) as more risk activities with house (48.9%) and school (13.7%) as highest risk area for foodborne outbreak. Homemade food (46.9%) and catering food (18.9%) as highest causes of cases with pathogen bacterial as frequent agent (74.9%) such as E.coli. The most contributing factor was inadequate cooking and storage at inappropriate temperature.ConclusionHigh risk population of foodborne outbreak was women with pathogen bacterial as the highest agent. The most contributing factor was pathogen resistance and growth. It need to increase monitoring and food-handler as food safety standard.